HIGH CAROTID RADIAL PULSE WAVE VELOCITY MAY BE CONNECTED TO LOWER QUALITY OF LIFE MEASURED BY SF-36 QUESTIONNAIRE. (June 2018) - Kantola, I.; Tervo, J.; Koskio, L.; Haijanen, J.; Hermansson, H.; Kantola, T.; Merikari, M.; Mäkelä, P.; Rehunen, S.; Varis, J.
Abstract : Objective: To clarify correlation of carotid-femoral (C-F) and carotid-radial (C-R) pulse wave velocity (PWV) to quality of life measured by SF-36 questionnaire and the explanatory factors of C-F and C-R PWV in Finnish drug-treated hypertensive patients. Design and method: A Doppler ultrasonography device (Micro Medical PulseTrace PWV, Micro Medical Ltd, Rochester, Kent, UK) was used to measure C-F and C-R PWV in 133 Finnish drug-treated hypertensive patients, The mean age was 65.0 (8.8) years (59 females and 74 males). 24 hour ambulatory blood pressure monitoring (ABPM) was performed with a portable device (90207 Ambulatory Blood Pressure Monitor, SpaceLabs Inc., Washington, U.S.). SF-36 questionnaire was used in calculating quality of life. Fasting plasma glucose, GHbA1c, lipids and urine albumin/creatinine ratio were measured. Results: C-F PWV did not correlate to any SF-36 parameter. C-R PWV correlated inversely to SF-36 vitality, social functioning and mental health. The mean 24 hour systolic blood pressure (SBP) was 132.5 (12.1) and diastolic blood pressure (DBP) 76.4 (6.9) mmHg. The mean C-F PWV was 11.4 (3.8) m/s and C-R PWV 11.5 (2.5) m/s. C-F PWV correlated positively to age, office systolic blood pressure and serum creatinine. C-R PWV correlated positively to height, weight, waist-hip ratio, male gender and glycosylated haemoglobin A1c (GHbA1c) and negatively to SF-36 questionnaire vitality, social functioning and mental health, female gender, plasma total and LDL-cholesterol. According to stepwise linear regression analysis C-F PWV was explained by SF-36 bodily pain (t = 2.141, p = 0.038), office SBP (t = 3.056, p = 0.04) and 24 hour heart rate standard deviation (t = −2.244, p = 0.030) and C-R PWV by weight (t = 2.898, p = 0.005), GHbA1c (t = 2.700, p = 0.009) and male gender (t = 2.077, p = 0.041). Conclusions: Among treated Finnish hypertensive patients C-R PWV was correlated to SF-36 questionnaire parameters vitality, social functioning and mental health which may suggest that high C-R PWV may decrease quality of life of these patients. Also C-F PWV was partly explained by SF-36 bodily pain which suggest that C-F PWV might be high in patients with less pain.